Maternal pregnancy hypertension impairs nitric oxide formation and results in increased arterial blood pressure in first-generation offspring female rats - Bozoni, Filipe Trindade [UNESP]; Santos, Natália Calixto Miranda [UNESP]; de Souza Paula Caetano, Ediléia [UNESP]; Mariani, Noemia Aparecida Partelli [UNESP]; da Rocha, Ananda Lini Vieira [UNESP]; Silva, Erick José Ramo [UNESP]; Dias-Junior, Carlos Alan [UNESP] (Elsevier, 2024)
Objectives: Maternal endothelial dysfunction in pregnancy hypertension is related to impairment of nitric oxide (NO) formation. However, NO levels and hemodynamic repercussions on the female offspring remain unclear. Therefore, this study hypothesized that maternal pregnancy hypertension reduces circulating NO metabolites and increases arterial blood pressure in first-generation offspring female rats. Study design: Descendant female rats were distributed in four groups as follows: virgin offspring of normotensive (VN) and hypertensive (VH) mothers and pregnant offspring of normotensive (PN) and hypertensive (PH) mothers. Hemodynamic and biochemical analyses were performed. Main outcome measures: The systolic (SBP) and diastolic (DBP) blood pressure, heart rate (HR), and body weight were measured. NO metabolites in plasma, NO formation in human umbilical vein endothelial cells (HUVECs) incubated with plasma, and endothelial NO synthase (eNOS) expression in aortas were determined. Results: Increased SBP, DBP, and reduced HR were found on the 60 days of life in the VH group, whereas the PH group showed increased SBP and HR on pregnancy day 7. All groups showed no differences in body weight gain and eNOS expression. Plasma levels of NO metabolites were increased in the PN compared to the other groups. Increases in the NO formation were greater in HUVECs incubated with plasma from VN and PN groups compared to the VH and PH groups. Conclusions: Female virgin and pregnant first-generation offspring rats from hypertensive pregnant mothers may have negative cardiovascular repercussions featured by increases in SBP, and possibly impaired NO formation is involved.
Keywords: Endothelium; Female offspring; Hemodynamic parameters; Nitric oxide; Pregnancy hypertension